Islamic Insurance Services in Riau Province: a Customer Satisfaction Survey - Bakhri, Boy Syamsul (Adpebi Science Series, 2022)
This study is motivated by curiosity about Islamic insurance services in Riau Province. Survey technique is used in data collection in this study. The population is Islamic insurance customers in this province and the samples in this study refer to the calculation of Hair et al with total assets of Islamic insurance as a consideration in determining proportional allocation. Sources of data in this study are primary data (data collection techniques using questionnaires) and secondary data (collection of relevant documents). The data analysis technique uses descriptive statistics with a frequency distribution (presented using table). The results of the study found that the most Islamic insurance customers are satisfied with various aspects of the services provided by Islamic insurance, while the five service aspects whith the highest level of customer satisfaction are Islamic insurance staff friendliness, advice given by Islamic insurance employees, Islamic insurance name and image, confidentially Islamic insurance customer data, as well as various kinds of facilities offered by Islamic insurances.